Feasibility and construct validation of the patient reported outcomes measurement information system in systemic vasculitis - Tomasson, G; Farrar, JT; Cuthbertson, D; McAlear, CA; Ashdown, S; Cronholm, PF; Dawson, J; Gebhart, D; Lanier, G; Luqmani, RA; Milman, N; Peck, J; et al. (Journal of Rheumatology Publishing Co Ltd, 2019)
OBJECTIVE: The Patient Reported Outcome Measurement Information System (PROMIS) is a collection of item banks of self-reported health. This study assessed the feasibility and construct validity of using PROMIS instruments in vasculitis. METHODS: Data from a multicenter longitudinal cohort of subjects with systemic vasculitis were used. Instruments from 10 PROMIS item banks were selected with direct involvement of patients. Subjects completed PROMIS instruments using computer adaptive testing (CAT). The Short Form 36 (SF-36) was also administered. Cross-sectional construct validity was assessed by calculating correlations of PROMIS scores with SF-36 measures and physician- and patient global scores for disease activity. Longitudinal construct validity was assessed by correlations of between-visit differences in PROMIS scores with differences in other measures. RESULTS: During the study period 973 subjects came for 2,306 study visits and the PROMIS collection was completed at 2,276 (99%) of visits. The median time needed to complete each PROMIS instrument ranged from 40-55 seconds. PROMIS instruments correlated crosssectionally with individual scales of the SF-36, most strongly with subscales of the SF-36 addressing the same domain as the PROMIS instrument. For example, PROMIS Fatigue correlated with both the Physical Component Score (PCS) (r=-0.65) and with the Mental Component Score (MCS) (r=-0.54). PROMIS Physical Function correlated strongly with PCS (r=0.81) but weakly with MCS (r=0.29). Weaker correlations were obse¬rved longitudinally between change in PROMIS scores with change in PCS and MCS. CONCLUSION: Collection of data using CAT PROMIS instruments is feasible among patients with vasculitis and has some cross-sectional and longitudinal construct validity.